2020
DOI: 10.1021/acsami.0c14889
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Roll-to-Roll-Coated Cantilever-Structured Touch Sensors

Abstract: It is common in the field of printed electronics that polydimethylsiloxane (PDMS) be used as a dielectric layer for capacitive sensors because of its high elasticity and restoration force. However, capacitive sensors with the PDMS dielectric layer have a lower sensitivity than those with an air-gap structure that has been fabricated by the conventional micro-electromechanical system (MEMS) process. This paper presents a productive method for fabricating air-gap structures for touch sensors by roll-to-roll slot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…A productive roll-to-roll printed method for fabricating touch sensors (shown in Fig. 5 c) [ 41 , 147 ]. The bottom electrode, the dielectric, and the sacrificial layers were coated on a flexible substrate by roll-to-roll slot-die, while the roll-to-roll gravure printing was used to form the top electrode.…”
Section: Fabrications Of the Flexible Ofets-based Sensorsmentioning
confidence: 99%
“…A productive roll-to-roll printed method for fabricating touch sensors (shown in Fig. 5 c) [ 41 , 147 ]. The bottom electrode, the dielectric, and the sacrificial layers were coated on a flexible substrate by roll-to-roll slot-die, while the roll-to-roll gravure printing was used to form the top electrode.…”
Section: Fabrications Of the Flexible Ofets-based Sensorsmentioning
confidence: 99%
“…In CFM (Clear and Nealey 1999;Takano et al, 1999;Okabe et al, 2000;Fiorini et al, 2001;Kreller et al, 2002;Brewer and Leggett 2004;Gourianova et al, 2005;Cameron et al, 2006;Dague et al, 2007;Dufrene 2008;Foster et al, 2009;Sirghi et al, 2009;Barattin and Voyer 2011;Teobaldi et al, 2011;Alsteens et al, 2012;Picas et al, 2012;Beaussart et al, 2014;Hibino and Nakano-Nishida 2014), cantilever tips are chemically functionalized with particular functional groups for performing specific functions in a system. CFM relies on two approaches: microcantilever-based biosensors (MC-B) (Subramanian and Catchmark 2007;Lang and Gerber 2008;Gruber et al, 2011;Johnson and Mutharasan 2012;Peiner and Wasisto 2019;Bennett et al, 2020;Lee and Lee 2020;Mamou et al, 2021) and nanomechanical cantilever sensors (NCS) to achieve these goals of characterizing and understanding the system at single-molecule level with high reproducibility and repeatability. The microcantilever-based biosensing utilizes the specific binding of biomolecules for analytical sensing.…”
Section: Afm As Biosensormentioning
confidence: 99%
“…However, many other applications, such as implantable cerebrovascular and arterial stents, brain–machine interfaces, and fully printed wearable devices, are of tremendous interest [ 10 , 150 ]. Other systems have been successfully fabricated with high throughput methods, as summarized in Table 4 [ 37 , 129 , 162 , 163 , 164 , 165 , 166 ]. One area of critical interest is wearable electrophysiology monitoring.…”
Section: Applications For Bioelectronicsmentioning
confidence: 99%
“…Another interesting area of research is the development of capacitive touch sensors, which have been widely reported in the literature using traditional MEMS fabrication. Lee et al created such a touch sensor with an air gap instead of PDMS dielectric, and noted that the increased dielectric constant of air allowed for highly improved sensitivity (ΔC/C 0 (%) of 0.118%) and high linear sensing range from 0–20 KPa [ 37 ]. One area of high interest is in printing on TPU substrates, and this was the focus of a recent investigation by Jansson et al using screen-printed AgNP inks.…”
Section: Applications For Bioelectronicsmentioning
confidence: 99%
See 1 more Smart Citation